Surface figure metrology for reflective membrane mirrors based on phase-measuring deflectometry - Yan, Xin; Zhuang, Zhi-Kang; Du, Fu-Jia; Duan, Wen; Yin, Peilin; Yu, Mo-Nong; Yang, Guang (Frontiers in Astronomy and Space Sciences, 2026)
Reflective membrane mirrors provide a lightweight, low-cost alternative to traditional optics for next-generation large-aperture telescopes, but their non-rigid, thin structure poses challenges for surface metrology. We present a phase-measuring deflectometry (PMD) system enhanced with tailored ray-tracing and iterative reconstruction to enable non-contact measurement of large membrane optics. The system successfully characterizes the surface figure and evaluates the dynamic stability of a 1-m Hencky-type membrane mirror. Our results demonstrate the effectiveness of PMD as a practical metrology tool for future membrane-based telescope systems.